The Motion and Deposition of Small Particles in the Human Lung Acinus, Part B: Weibel’s Model of Bifurcating Airways - Vanunu, Yakir; Haber, Shimon (British Journal of Healthcare and Medical Research, 2023)
Weibel’s model A for the human lung is applied in which the lung comprises a binary bifurcating tree of 23 generations of airways. It assumes that each airway bifurcates into two airways their sizes defined by the generation number. The goal of this analysis is to predict deposition efficiencies of various size particles which reach the human acinus vis-a-vis generation number, a result that can be used in designing inhaled therapeutical particles or preventing dangerous substances like Covid 19 of reaching the blood stream. The simulations account for particle convection, the effects of gravity and Brownian motion. Applying ANSYS Fluent, a commercial program which includes a two-phase model for finite volumes, it is found that particle diameters within the range (0.4 ¸ 1.0 mm) and densities as low as 500 kg/m3 reach deep into the human lung acinus and are likely to reach the blood stream. Particles of higher densities and diameters outside the foregoing range deposit at lower branches of the acinar tree, the smaller particles due to dominant diffusion and the bigger due to gravity.